Bacteriologic Profile of the Conjunctiva in the Patients with Dry Eye - Hori, Yuichi; Maeda, Naoyuki; Sakamoto, Masako; Koh, Shizuka; Inoue, Tomoyuki; Tano, Yasuo (American journal of ophthalmology, 2008)
To assess the conjunctival bacterial profiles in dry eye and their fluoroquinolone susceptibility patterns. Prospective, observational study. Sixty-seven female patients with dry eye (29 with Sjögren syndrome and 38 without Sjögren syndrome) who received artificial tears were enrolled at Osaka University Hospital in Japan. Twenty-three patients received additional topical steroids. Twenty-six puncta were occluded with plugs. Cultures were obtained with conjunctival swabs at the right eye of the subjects. The minimum inhibitory concentrations of isolated strains were determined for the fluoroquinolones (levofloxacin and gatifloxacin). The profiles of conjunctival bacteria of patients with dry eye were compared with those obtained before surgery from 56 female control patients. Eighty-eight strains were isolated (48 strains of Propionibacterium acnes, 26 coagulase-negative Staphylococcus [CNS] species, six Staphylococcus aureus strains, and eight others). Of the 26 CNS strains, 17 (65.4%) were fluoroquinolone resistant, including four (33.3%) of 12 methicillin-sensitive CNS and 13 (92.9%) of 14 methicillin-resistant CNS. All methicillin-sensitive S. aureus strains and P. acnes strains were sensitive to fluoroquinolones; one methicillin-resistant S. aureus strain was resistant. There was no significant difference in the conjunctival isolation rates between patients with dry eye and controls. However, the dry eye group had a significantly higher incidence of fluoroquinolone-resistant methicillin-sensitive CNS and of fluoroquinolone-resistant methicillin-resistant CNS than controls ( P = .018 and P = .024, respectively). There were no significant differences in bacteria isolated between subgroups with or without punctal plugs and with or without topical steroids. Patients with dry eye are more likely to have fluoroquinolone-resistant conjunctival bacteria than controls. These results may help prevent infectious keratoconjunctivitis in patients with dry eye.